Assessment of pharmaceutical equivalence of topical cream products containing hydrocortisone acetate using in vitro release testing (IVRT) - Mudyahoto, Nyengeterai Amanda (Rhodes University, Faculty of Pharmacy, Pharmacy, 2018)
Expected release date-April 2020
Keywords: Uncatalogued